Learning to say good-by : when a parent dies - LeShan, Eda J.; Giovanopoulos, Paul. (New York : Macmillan, 1978)
Discusses the questions, fears, and fantasies many children experience when a parent or someone close to them dies.
Bibliography: p. 83-85.
Keywords: Bereavement -- Psychological aspects -- Juvenile literature; Parents -- Death -- Psychological aspects; Death